The effect of buccal corticotomy on accelerating orthodontic tooth movement of maxillary canine - Mohammad Reza Jahanbakhshi; Ali Mohammad Kalantar Motamedi; Masoud Feizbakhsh; Ahmad Mogharehabed (Wolters Kluwer Medknow Publications, 2016)
Background: Selective alveolar corticotomy is defined as an intentional injury to cortical bone. This technique is an effective means of accelerating orthodontic tooth movement. The aim of this study is to evaluate the effect of buccal corticotomy in accelerating maxillary canine retraction. Materials and Methods: The sample in this clinical trial study consisted of 15 adult female patients with therapeutic need for extraction of maxillary first premolars and maximum canine retraction. By use of split-mouth design, at the time of premolars extraction, buccal corticotomy was performed around the maxillary first premolar, randomly on one side of maxilla, and the other side was reserved as the control side. Canine retraction was performed by use of friction - less mechanic with simple vertical loop. Every 2 weeks, distance between canines and second premolars was measured until complete space closure. The velocity of space closure was calculated to evaluate the effect of this technique in accelerating orthodontic tooth movement. The obtained data were statistically analyzed using independent t-test, and the significance was set at 0.05. Results: The rate of canine retraction was significantly higher on the corticotomy side than the control side by an average of 1.8 mm/month versus 1.1 mm/month in the corticotomy side and control side, respectively (P < 0.001). Conclusion: Based on result of this study, corticotomy can accelerates the rate of orthodontic tooth movement about two times faster than conventional orthodontics and it is significant in early stages after surgical porsedure. Therefore Buccal corticotomy is a useful adjunct technique for accelerating orthodontic tooth movement.